2002
DOI: 10.1093/brain/awf071
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced inactivation and pH sensitivity of Na+ channel mutations causing hypokalaemic periodic paralysis type II

Abstract: Hypokalaemic periodic paralysis (hypoPP) is a dominantly inherited muscle disorder characterized by episodes of flaccid weakness. Previous genetic studies revealed mutations in the voltage-gated calcium channel alpha1-subunit (CACNA1S gene) in families with hypoPP (type I). Electrophysiological studies on these mutants in different expression systems could not explain the pathophysiology of the disease. In addition, several mutations (Arg669His, Arg672His, Arg672Gly and Arg672Ser) in the voltage sensor of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 32 publications
1
51
0
1
Order By: Relevance
“…55 Here, the mechanism might also involve regulation of potassium ion and proton concentrations. To determine whether a change of the proton concentration influences the gating of SCN4A mutants, Kuzmenkin et al 59 used pH values ranging from 6.4 to 8.4 in bath or pipette solutions. The change of extracellular pH had profound effects on steady-state activation and inactivation of the wild-type channels, probably due to the change in surface potential but also to a direct blockade of the sodium channels.…”
Section: Acetazolamidementioning
confidence: 99%
“…55 Here, the mechanism might also involve regulation of potassium ion and proton concentrations. To determine whether a change of the proton concentration influences the gating of SCN4A mutants, Kuzmenkin et al 59 used pH values ranging from 6.4 to 8.4 in bath or pipette solutions. The change of extracellular pH had profound effects on steady-state activation and inactivation of the wild-type channels, probably due to the change in surface potential but also to a direct blockade of the sodium channels.…”
Section: Acetazolamidementioning
confidence: 99%
“…The convergence of these mutations on the outermost two gating charges of voltage sensors in two different proteins strongly implicates voltage sensor dysfunction in this disease. Standard electrophysiological studies of these mutant sodium channels expressed in heterologous cells revealed only mildly enhanced fast and/or slow inactivation (9)(10)(11)(12), but more sensitive recordings in the cutopen oocyte preparation showed that HypoPP mutant Na V 1.4 channels conduct gating pore currents caused by movement of protons and cations through the mutant voltage sensor (13,14). Gating pore current constitutes a gain-of-function effect because steady influx of cations at resting membrane potential would cause depolarization and sodium overload that impair action potential generation.…”
mentioning
confidence: 99%
“…Biophysical parameters suggest a loss of function effect, an enhanced slow inactivation being most frequently observed, in contrast with sodium channel mutations causing other types of periodic paralysis where a gain-of-function was demonstrated. 42,46,[49][50][51] Accordingly, recording of muscle fibers obtained from muscle biopsies showed a reduced current density and a slower upstroke and decreased action potentials when compared with controls. 42 As for the calcium channel, these observations are insufficient to understand how sodium channel mutations could provoke muscle fiber paralysis induced by depolarization and hypokalemia.…”
Section: 44mentioning
confidence: 97%